Rotation in 2D

Geometry Level pending

Two points A ( 1 , 0 ) , B ( 2 , 3 ) A(1, 0) , B(-2, -3) undergo a rotation in the x y xy plane about an unknown point in the plane, and through an unknown angle of rotation. However, we know their images under this rotation. The images are, A ( 2 , 3 ) , B ( 1 , 6 ) A'(-2,3) , B'(1, 6) . Find the image of the point C ( 4 , 5 ) C(4, 5) under the same rotation. If the image is C ( x , y ) C'(x, y) then enter the sum x + y x + y .


The answer is -7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

David Vreken
Jul 21, 2020

A rotation of a point ( x , y ) (x, y) about a point ( h , k ) (h, k) by an angle θ \theta to a new point ( x , y ) (x', y') is given by:

x = ( x h ) cos θ + ( y k ) sin θ + h x' = (x - h) \cos \theta + (y - k) \sin \theta + h

y = ( x h ) sin θ + ( y k ) cos θ + k y' = -(x - h) \sin \theta + (y - k) \cos \theta + k

If A ( 1 , 0 ) A(1, 0) rotates to A ( 2 , 3 ) A'(-2, 3) , then:

2 = ( 1 h ) cos θ + ( 0 k ) sin θ + h -2 = (1 - h) \cos \theta + (0 - k) \sin \theta + h

3 = ( 1 h ) sin θ + ( 0 k ) cos θ + k 3 = -(1 - h) \sin \theta + (0 - k) \cos \theta + k

And if B ( 2 , 3 ) B(-2, -3) rotates to B ( 1 , 6 ) B'(1, 6) , then:

1 = ( 2 h ) cos θ + ( 3 k ) sin θ + h 1 = (-2 - h) \cos \theta + (-3 - k) \sin \theta + h

6 = ( 2 h ) sin θ + ( 3 k ) cos θ + k 6 = -(-2 - h) \sin \theta + (-3 - k) \cos \theta + k

These four equations solve to h = 1 2 h = -\frac{1}{2} , k = 3 2 k = \frac{3}{2} , cos θ = 1 \cos \theta = -1 , and sin θ = 0 \sin \theta = 0 , so that this particular rotation is given by:

x = ( x + 1 2 ) ( 1 ) + ( y 3 2 ) ( 0 ) 1 2 = x 1 x' = (x + \frac{1}{2})(-1) + (y - \frac{3}{2})(0) - \frac{1}{2} = -x - 1

y = ( x + 1 2 ) ( 0 ) + ( y 3 2 ) ( 1 ) + 3 2 = y + 3 y' = -(x + \frac{1}{2})(0) + (y - \frac{3}{2})(-1) + \frac{3}{2} = -y + 3

Therefore, C ( 4 , 5 ) C(4, 5) will rotate to:

x = x 1 = 4 1 = 5 x' = -x - 1 = -4 - 1 = -5

y = y + 3 = 5 + 3 = 2 y' = -y + 3 = -5 + 3 = -2

in other words, to C ( 5 , 2 ) C'(-5, -2) . Therefore, x = 5 x = -5 , y = 2 y = -2 , and x + y = 7 x + y = \boxed{-7} .

The overall transformation matrix is

M = T 1 R T M=T^{-1}RT , where T = ( 1 0 x 1 0 1 y 1 0 0 1 ) T=\begin {pmatrix} 1 & 0 & -x_1\\0 & 1 & -y_1\\0 & 0 & 1\end {pmatrix}

is the translation matrix, T 1 T^{-1} is it's inverse, and

R = ( cos θ sin θ 0 sin θ cos θ 0 0 0 1 ) R=\begin {pmatrix} \cos \theta & \sin \theta & 0\\ -\sin \theta & \cos \theta & 0\\0 & 0 & 1\end {pmatrix}

is the matrix of rotation.

Using this and the transformation equation

X = M X X'=MX where X = ( x y 1 ) , X = ( 4 5 1 ) X'=\begin {pmatrix} x\\y\\1\end {pmatrix},X=\begin {pmatrix}4\\5\\1\end {pmatrix}

we get

M = ( 1 0 1 0 1 3 0 0 1 ) M=\begin {pmatrix} -1 & 0 & -1\\0 & -1 & 3\\0 & 0 & 1\end {pmatrix} ,

and X = ( 5 2 1 ) X'=\begin {pmatrix} -5 \\ -2 \\1\end {pmatrix}

So, x = 5 , y = 2 , x + y = 7 x=-5,y=-2,x+y=\boxed {-7} .

Qweros Bistoros
Jul 21, 2020

Let D = A A B = ( 4 , 3 ) D=A-\overrightarrow{AB}=(4,3) then D = A A B = ( 5 , 0 ) D'=A'-\overrightarrow{A'B'}=(-5,0)

Let F = A 5 3 A B = ( 6 , 5 ) F=A-\frac{5}{3}\overrightarrow{AB}=(6,5) then F = A 5 3 A B = ( 7 , 2 ) F'=A'-\frac{5}{3}\overrightarrow{A'B'}=(-7,-2)

As C D = C D C'D'=CD so ( x + 5 ) 2 + y 2 = ( 4 4 ) 2 + ( 5 3 ) 2 = 4 (x+5)^2+y^2=(4-4)^2+(5-3)^2=4

As C F = C F C'F'=CF so ( x + 7 ) 2 + ( y + 2 ) 2 = ( 4 6 ) 2 + ( 5 5 ) 2 = 4 (x+7)^2+(y+2)^2=(4-6)^2+(5-5)^2=4

After subtracting this equation we get 2 ( 2 x + 12 ) + 2 ( 2 y + 2 ) = 0 4 ( x + y + 7 ) = 0 x + y = 7 2(2x+12)+2(2y+2)=0 \Rightarrow 4(x+y+7)=0 \Rightarrow x+y=-7

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...